Impact of Religious Institutions on The Development of Southern Division Kabale Municipality. - Aryatuha, Cosmas (Kabale University, 2024)
The study investigated the impact of religious institutions on the development of the southern division, of Kabale "municipality. The study was guided by three objectives which include.' To analyze the contribution of religion to the development of the southern division, to find out whether religion has hindered or fostered the development of the southern division, and to identify other factors responsible for the development of the southern Division of Kabale municipality. The study was conducted using descriptive and analytical study design. A sample of 50 respondents was used to gather the required information and both stratified sampling and simple random methods were employed in selecting the sample. Questionnaires were administered to the respondents to gather the required data. The data was analyzed using Excel frequency distribution tables to establish the relationship between the variables. The study concludes that; the role of religion in development includes conflict prevention, peace building, governance, wealth creation, health, and education. Hindrances of development brought about by religion were personal interest, feelings, church wrangles, favoritism, change in modernization, and policy formulation. Other factors that affect development include; discrimination, population, culture, poor management, corruption, and political instability. The study recommends that there is a need to address the various challenges and appreciate the various contributions made by religion as far as development is concerned in the southern Division of Kabale municipality, there is also a need for religious leaders to convert people to embrace religious values to change their interests of worldly pleasures.